Treatment Responses of Cognitive Function and Plasma Asymmetric Dimethylarginine to Atypical Antipsychotic in Patients With Schizophrenia - Yu, Zhi-min; Zhao, Ying; Zhan, Jin-qiong; Luo, Tao; Xiong, Jian-wen; Yu, Bin; Wei, Bo; Yang, Yuan-jian (Frontiers in Psychiatry, 2019)
Cognitive deficits represent a core feature of schizophrenia. Previous studies have demonstrated that plasma asymmetric dimethylarginine (ADMA) was increased in patients with schizophrenia and correlated with cognitive impairments. Atypical antipsychotics can produce cognitive benefits in schizophrenia patients. In this study, we conducted a prospective observation trial to explore whether plasma ADMA may serve as an indicator for evaluating cognitive improvements induced by atypical antipsychotics in patients with schizophrenia. A total of 41 schizophrenia patients with acute exacerbation were enrolled and 29 patients completed this study. These recruited patients were drug-naive or had no exposure to antipsychotics for at least 3 months. Thirty healthy individuals were recruited as a control group. Positive and Negative Syndrome Scale (PANSS) and a neuropsychological battery were used to evaluate schizophrenic symptoms and cognitive function respectively. Plasma ADMA was measured by high-performance liquid chromatography (HPLC). We found that schizophrenia patients with acute exacerbation had significantly poorer cognitive performances and higher plasma ADMA levels than control individuals (p < 0.05). After two months of atypical antipsychotic treatment, patients showed significant improvements in processing speed, working memory, attention and executive function (all p < 0.01). Plasma ADMA levels in patients after treatment were significantly decreased compared to baseline (2.42 ± 0.84 vs. 1.55 ± 0.34 μmol/L; t = 6.491, p < 0.001). Correlation analysis reveals that there is a significant correlation of the decrease in ADMA with improvements in working memory (r = -0.413, p = 0.026) and attention (r = -0.417, p = 0.025). Collectively, our results suggest that atypical antipsychotic improves cognitive function in schizophrenia patients with acute exacerbation, in parallel with decreased plasma ADMA levels. Plasma ADMA levels might be an indicator for cognitive recovery in schizophrenia.